The factors of enhancing Graduate Teaching Assistants' Technological Pedagogical Content Knowledge (TPACK) performance in engineering curriculum teaching - Dedi Liu (Springer, 2022)
Abstract Graduate teaching assistants (GTAs) play important roles in engineering education at the undergraduate level. Since there are lots of technological content knowledge (TCK) in engineering curriculums, the improvements of GTAs' teaching skills on TCK will help the teaching effectiveness of the curriculums. As the instructor's knowledge about technology-infused instruction for TCK is the core of the teaching skill, Technological Pedagogical Content Knowledge (TPACK) is taken as a framework to measure the extent to which instructor can teach with technology. In this study, an online questionnaires survey covering GTAs' program coordinator, teacher, graduate student and undergraduate student has done to explore the factors of enhancing GTAs' TPACK performance. The quantitative analyses through a structural equation modeling approach indicates that the roles of the GTAs should be clearly recognized by the teacher, program coordinators and GTAs themselves. An evaluating procedure for GTAs should be established; The attitude and self-efficacy of GTAs should be improved through the training courses and the field trips while the promising expectation from the undergraduate student on the roles of GTAs can improve the performance of GTAs' program. Our results will be helpful not only for engineering curriculum, but also for other curriculums.